The circular economy and mining workwear waste management in Australia: A case study - Zaman, Atiq; Marinova, Dora; Farren, Anne (2023)
End-of-life uniforms and workwear account for around 11,000 tonnes of textile waste in Australia and only 1 per cent is recycled, with the rest discarded in landfills. Australia’s large mining industry operations do not currently engage in responsible employee uniforms and workwear management contributing to the problem of waste. In 2021, the Commonwealth Government of Australia supported the development of a product stewardship scheme to recycle uniforms and workwear to be launched in 2022 and awarded A$1 million in funding to the Australian Fashion Council to implement a National Clothing Product Stewardship Scheme. These initiatives aim to improve the design, recovery, reuse and recycling of textiles, providing a roadmap to achieve clothing circularity in Australia by 2030 in line with the National Waste Policy Action Plan targets. The mining industry is the engine of the Australian economy, contributing to economic performance, employment, exports and tax revenues. With the country having some of the largest reserves of iron ore (#1 worldwide), gold (#2 worldwide), silver (#3 worldwide) and lithium (#2 worldwide), the importance of mining and the employment options it provides will continue to grow, particularly in transitioning to a net-zero economy. Urgent solutions are needed to address the issues surrounding uniform and workwear use to eliminate the substantial amounts of textile waste currently generated by the mining industry. This article presents a case study in Western Australia, where half of Australia’s mining operations are located, examining the potential for reducing the mining industry’s garment waste by applying the circular economy principles. The findings from the case study will assist in better understanding the current practices, key challenges and potential opportunities in upcycling and recycling mining workwear in Western Australia.